Construction of helical coordination polymers via flexible conformers of bis(3-pyridyl)cyclotetramethylenesilane: metal(ii) and halogen effects on luminescence, thermolysis and catalysis1. Issue 17 (7th May 2015) - Kim, Hyeun; Park, Minwoo; Lee, Haeri; Jung, Ok-Sang
<x xml:space="preserve">Abstract</x> Construction and physicochemical properties of rectangular-tubular-helical coordination polymers of [M(ii)X2L] (M = Zn(ii), Hg(ii); X− = Cl−, Br−) were investigated.